2006
DOI: 10.1348/096317905x70823
|View full text |Cite
|
Sign up to set email alerts
|

Incongruence as an explanation for the negative mental health effects of unemployment: Meta‐analytic evidence

Abstract: The present paper is concerned with the effects of incongruence between a person's level of employment commitment (measured with scales of work involvement, Protestant work ethic or similar concepts) and his or her current employment situation (employed or not employed). We hypothesize that this kind of incongruence (a) is a typical characteristic of the unemployment situation and (b) is systematically associated with diminished well‐being and mental health. Meta‐analyses of empirical data endorse both hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
106
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(119 citation statements)
references
References 87 publications
(89 reference statements)
8
106
0
4
Order By: Relevance
“…Numerous studies have shown an association between unemployment and poor mental health status [32], although few have specifically focused on the problems faced by unemployed parents and their health outcomes [29]. Notably, parent job loss and inability to meet mortgage payments were not found to be cooccurring events within the current analysis, suggesting that their relationship with high respondent distress represents distinct phenomena.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Numerous studies have shown an association between unemployment and poor mental health status [32], although few have specifically focused on the problems faced by unemployed parents and their health outcomes [29]. Notably, parent job loss and inability to meet mortgage payments were not found to be cooccurring events within the current analysis, suggesting that their relationship with high respondent distress represents distinct phenomena.…”
Section: Discussionmentioning
confidence: 59%
“…Possibly more important to the economic security of Western Sydney households, however, are longer-term structural factors affecting the region; jobs "shortfalls," transport inequities, lower average incomes (affecting financial accumulation), and associated mortgage/housing "distress." Although household financial strain can adversely affect the psychosocial development of children [4,5], less is known about the relative effects of such hardship on parental mental health, particularly populations that may have greater exposure to economic downturns and threats to employment [14,29]. Overall, our findings show that when controlling for other potential confounders, financial stressors showed the strongest relationship with high parental psychological distress.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Similarly, research on work-related over-commitment found that health complaints resulting from a lack of balance between efforts put into one's job and rewards received are stronger when commitment is high (Aust et al, 1999;Joksimovic et al, 1999). Finally, employment commitment aggravates the negative effects of unemployment on mental health (Paul & Moser, 2006). All of this evidence suggests that being committed moderates the negative effects of change and transitions.…”
Section: Interaction Of Commitment and Reassignment On Well-beingmentioning
confidence: 93%
“…Besides socio-demographic variables, work involvement was the only characteristic in our model measured only at the first time point. We based this decision on the meta-analysis of longitudinal data which showed that average test-retest correlation of work involvement is relatively high (r=0.59 for the average time period of 9.4 months, Paul & Moser, 2006), indicating a stable, trait-like construct. Cronbach α for this scale was 0.75.…”
Section: Work Involvementmentioning
confidence: 99%